Vilniaus universiteto bibliotekos nepublikuotų bibliografinių priemonių fondas - Petrauskienė, Zofija Milda (Knygotyra, 1983)
The development of a subsidiary scientific bibliography is one of the main tasks of a higher school library. Since 1944 planned speciae bibliographical aids have been prepared at the Scientific library of Vilnius university. Their subject matter is determined by the University profile and its scientific and educational objectives. Some of the prepared works are published, the rest remains unpublished and is preserved in the storage collection of the Bibliographical department. Thematic bibliographical aids are also compiled during bibliographical services to the readers by an “order-answer” regime. The collection of unpublished bibliographical aids in the library forms one part of its reference system. The content of the collection is shown by means of alphabetical, subject and personalia card files. Information about newly compiled bibliographical aids is regulary sent to the State library of the Republic. The collection includes 424 bibliographical aids with the total volume of 85 thousand printed positions. There dominate lists and indices from the study of local lore and personalia. Thematic distribution of the collection shows that the aids on humanitarian subjects form the bulk of the collection. The collection includes vast material on Lithuanian history, economic development of Lithuania, its relations with the neighbouring countries, material about different localities and towns. The aim of bibliographical aids an social sciences is to facilitate the fulfilment of students’ education and ideology formation tasks. The collection includes extensive material on the history of science and education in Lithuania, secondary and higher school pedagogics, history of press and librarianship, literature and linguistics, questions of art. There are works on various questions on natural sciences and medicine as well. If larger indices and lists comprise questions on different related subjects, such bibliographical aids are reflected in all the divisions of the card file. The collection of unpublished bibliographical aids has been accumulated for nearly 40 years, so some aids include more recent publications, others include older ones. The bulk of indices and lists iis of a selective character. including works in the Lithuanian, Russian and foreign languages.